2022
DOI: 10.21931/rb/2022.07.03.25
|View full text |Cite
|
Sign up to set email alerts
|

Submission and Phylogenetical of Local Isolated Trichophyton interdigitale of Iraqi Patients in NCBI

Abstract: Dermatophytes are species with slight genetic variation, and are yet several uncertainties about the differences among species. This study aims to isolate and diagnose the Trichophyton interdigitale by molecular technique and to reveal the phylogenetic distance and similarity of the Iraqi isolates to other isolates from the globe, in addition, to submit the obtained sequences to the NCBI database. This study included 86 with multiple lesions on different parts of the body. The results showed different variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…[12] reported that they sequenced four T. mentagrophytes genomes and discovered that T. interdigitale & T. mentagrophytes are the same phylogenetic species. According to [13], T. interdigitale isolates are only anthropophilic, while zoophilic T. interdigitale isolates are T. mentagrophytes.T. interdigitale and T. mentagrophytes were identified as species complexes which might be affected by epigenetic change throughout human & animal body localization based on the overall average of intraspecies and interspecies pairwise distances of combination [14,15].…”
Section: The Phylogenetic Tree Of Trichophyton Spmentioning
confidence: 99%
“…[12] reported that they sequenced four T. mentagrophytes genomes and discovered that T. interdigitale & T. mentagrophytes are the same phylogenetic species. According to [13], T. interdigitale isolates are only anthropophilic, while zoophilic T. interdigitale isolates are T. mentagrophytes.T. interdigitale and T. mentagrophytes were identified as species complexes which might be affected by epigenetic change throughout human & animal body localization based on the overall average of intraspecies and interspecies pairwise distances of combination [14,15].…”
Section: The Phylogenetic Tree Of Trichophyton Spmentioning
confidence: 99%